A.G Noorani, The Kashmir Dispute 1947-2012 - Muhammad Faisal (CISS Insight Journal, 2014)
The Kashmir Dispute: 1947-2012, in two volumes is a collection of articles written by A.G. Noorani on developments related to India-Pakistan relations in the context of the Kashmir dispute. It opens with an insightful introduction meant to fuel a vibrant discussion on the nature, history and future of the dispute and inhabitants of the scenic state of Jammu and Kashmir. The book provides a comprehensive account of the dispute and various developments that have taken place from political, diplomatic, legal and humane perspectives. It relies on indepth research, extensive quotations from the original and archived documents and makes politically controversial revelations, aimed at forcing a rethink of traditional reading of the origin of the dispute and subsequent developments. Noorani, a senior advocate of the Indian Supreme Court and an acknowledged constitutional expert, has written extensively over last six decades on a variety of themes including Islam, India-Pakistan relations, domestic politics of India, Kashmir dispute, Indo-Pak wars, and the constitutional history of Jammu and Kashmir. This book is engaging andhighly readable. It connects various historical events and developments that may not appear to have any relation with each other. The main message of the book is that Kashmiri Muslims have been yearning for justice since 1947. Justice should have been done to them in later years, as it was not provided to them in 1947, when Pakistan stood for the right of selfdetermination of the people of Jammu and Kashmir. Thereafter, India refused to meet its commitment, of determining the future of the state through plebiscite, made to the people of Kashmir, the Indian people, and the United Nations.